Agile and Integrated Logistics (A strategic paper on Upbrofil Logistics Inc.) - Ruyeras, Ludwig B. (School of Management, University of the Philippines Mindanao, 2011)
UPBROFIL is a predominantly functional organization, yet it focuses on clients, products, and geography. The organization makes such use of its network and some activities are contracted out particularly on trucking services. The organization is relatively flat. It has good span of control as it has a centralized decision making system. It has extensive use of rules and procedures to organize and coordinate work activities. So far, the structure is working for the organization. But considering a fast-paced and ever dynamic industry, the company recognizes some points that it needs to improve on particularly on its weaknesses. ?Change has a considerable psychological impact on the human mind. To the fearful it is threatening because it means that things may get worse. To the hopeful it is encouraging because things may get better. To the confident it is inspiring because the challenge exists to make things better.?~ King Whitney Jr. Any industry is important for each country. It provides work, income and fights poverty. But we are in a competitive world. To maintain a good position, any sector will have to focus on the need to improve efficiency. Sometimes, logistics cost of a film is the last place where managers look for possible improvements or potential additional income. Among the objectives in developing this strategic paper was to improve the cohesiveness of decision-making, mastery of the art of choosing the most ?appropriate? appropriate response to the problems and situations being confronted and resource balancing in UPBROFIL Logistics, thus boosting the returns to stockholders. To achieve profit growth, it must work with their clients (Internal/External) ? as well as their existing technology and business practices-to further cutting of costs, to further improve customer service and to even capture potential clients. The paper articulate in specific terms strategies that are in line with the appraisal of the vision-mission statement, and goals of UPBROFIL Logistics and also considerations that were made based on the result of the exhaustive study of its internal and external environments. UPBROFIL seeks to distinguish itself by providing the most possible flexibility and reliability in customer service tailored to its clients? individual needs and time requirements. The organization is also into the fabrication of mechanical, storage and transportation equipment; Trading of various goods and commodities; and contracting for civil and structural works, land development, construction of bridges, irrigation and asphalting and lately, it expanded to Cement Trading under dealership relationship with LaFarge ? Mindanao Portland Cement Corporation. UPBROFIL is more than just a logistics company. The end goal of its endeavours is to delight both its internal and external customers by providing excellent service as well as introducing systems, processes or programs that will instil and sustain a work culture that promotes continuous improvement. The expansion was more on taking advantage of the opportunities upfront brought about by the networks we gained. Its operation is faring along smoothly and productively. The Key Strategies in this paper shall serve as the steering wheel for program implementation, supervision, evaluation and control which includes making out of common patterns and emerging trends as well as the verification of the root causes of the problems to assure superior execution and delivery of change management processes for UPBROFIL. UPBROFIL is a predominantly functional organization, yet it focuses on clients, products, and geography. The organization makes such use of its network and some activities are contracted out particularly on trucking services. The organization is relatively flat. It has good span of control as it has a centralized decision making system. It has extensive use of rules and procedures to organize and coordinate work activities. So far, the structure is working for the organization. But considering a fast-paced and ever dynamic industry, the company recognizes some points that it needs to improve on particularly on its weaknesses. ?Change has a considerable psychological impact on the human mind. To the fearful it is threatening because it means that things may get worse. To the hopeful it is encouraging because things may get better. To the confident it is inspiring because the challenge exists to make things better.?~ King Whitney Jr. Any industry is important for each country. It provides work, income and fights poverty. But we are in a competitive world. To maintain a good position, any sector will have to focus on the need to improve efficiency. Sometimes, logistics cost of a film is the last place where managers look for possible improvements or potential additional income. Among the objectives in developing this strategic paper was to improve the cohesiveness of decision-making, mastery of the art of choosing the most ?appropriate? appropriate response to the problems and situations being confronted and resource balancing in UPBROFIL Logistics, thus boosting the returns to stockholders. To achieve profit growth, it must work with their clients (Internal/External) ? as well as their existing technology and business practices-to further cutting of costs, to further improve customer service and to even capture potential clients. The paper articulate in specific terms strategies that are in line with the appraisal of the vision-mission statement, and goals of UPBROFIL Logistics and also considerations that were made based on the result of the exhaustive study of its internal and external environments. UPBROFIL seeks to distinguish itself by providing the most possible flexibility and reliability in customer service tailored to its clients? individual needs and time requirements. The organization is also into the fabrication of mechanical, storage and transportation equipment; Trading of various goods and commodities; and contracting for civil and structural works, land development, construction of bridges, irrigation and asphalting and lately, it expanded to Cement Trading under dealership relationship with LaFarge ? Mindanao Portland Cement Corporation. UPBROFIL is more than just a logistics company. The end goal of its endeavours is to delight both its internal and external customers by providing excellent service as well as introducing systems, processes or programs that will instil and sustain a work culture that promotes continuous improvement. The expansion was more on taking advantage of the opportunities upfront brought about by the networks we gained. Its operation is faring along smoothly and productively. The Key Strategies in this paper shall serve as the steering wheel for program implementation, supervision, evaluation and control which includes making out of common patterns and emerging trends as well as the verification of the root causes of the problems to assure superior execution and delivery of change management processes for UPBROFIL.